The Empire Within: Postcolonial Thought and Political Activism in Sixties Montreal - Lexier, Roberta (Labour / Le Travail, 2011)
The article reviews the book, "The Empire Within: Postcolonial Thought and Political Activism in Sixties Montreal," by Sean Mills.
Keywords: BOOKS – Reviews; EMPIRE Within: Postcolonial Thought & Political Activism in 60s Montreal; The (Book); History; MILLS; Sean; MONTREAL (Quebec); Nonfiction